Valdosta State College Baseball, 1983 - Valdosta State University, Athletics Department (Valdosta State University, 1983)
Valdosta State College Baseball, 1983. Program. 1983. 49-22 NCAA, Division II 8017D39F-4445-4005-BCE1-FFC6153C7565
Bill Grant; Dr. F. D. Toth; Dr. Joe Gore; Steve Roberts; Jim Madaleno; Tommy Thomas; Kip McLeod; Bart Shuman; James Gamber; John Lampert; Katrina Davis; Janet Scarborough; Jeff Agerter; Jerry Clark; Rick Dinapoli; Raymond Drennon; Kevin Faulkner; Wayne Fugett; Bobby Hurtt; Mike Jones; Mark Schanback; Ricky Tucker; Michael White; Mark Murad; Mike Ruff; Jeff Soss; Jimmy McWhorter; Charlie Moore; June Munford; Mark Powell; Rob Sullenberger; Greg Waits; Rob Busch; Bryan Clarridge; Chuck Devane; John Keigher;
Keywords: Athletics; Baseball